PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RUMAH MAKAN MM RESTO KARAWANG - Dedi Mulyadi (GoAcademica Research dan Publishing, 2019)
The purpose of this study was to determine and analyze the effect of product and service quality on customer satisfaction at MM Reso Karawang Restaurant either partially or simultaneously. This research uses quantitative methods that are verification. The research proves that simultaneously, product quality and service have a positive effect on customer satisfaction. While pasrial, product quality and service quality variables affect customer satisfaction. Partially, product quality has a greater influence on customer satisfaction than service quality.